2007
DOI: 10.1002/jnr.21433
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to dieldrin reduces γ‐aminobutyric acid type A and N‐methyl‐D‐aspartate receptor function in primary cultures of mouse cerebellar granule cells

Abstract: The organochlorine pesticide dieldrin is a persistent organic pollutant that accumulates in the fatty tissue of living organisms. In mammals, it antagonizes the GABAA receptor, producing convulsions after acute exposure. Although accumulation in human brain has been reported, little is known about the effects of long‐term exposure to dieldrin in the nervous system. Homeostatic control of the balance between excitation and inhibition has been reported when neuronal activity is chronically altered. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Although our TP/AOP has focused on excitotoxicity, many chemicals specifically disrupt inhibitory pathways, which will have consequences for the TP/AOP. For example, Babot et al [69] found that reduction of GABA(A) receptor function by dieldrin, an organochlorine insecticide, was followed by a decrease in NMDA receptor function as a compensatory response; and RDX, an explosive compound that causes seizures, has been shown to disrupt GABAergic signaling [125]. Application of the TP/AOP will not only enable us to better resolve the pathway/mechanisms/ risks for domoic acid, but similar assessments can be carried out for other chemicals that impact different points in the TP.…”
Section: Evaluating Model Predictive Capabilitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Although our TP/AOP has focused on excitotoxicity, many chemicals specifically disrupt inhibitory pathways, which will have consequences for the TP/AOP. For example, Babot et al [69] found that reduction of GABA(A) receptor function by dieldrin, an organochlorine insecticide, was followed by a decrease in NMDA receptor function as a compensatory response; and RDX, an explosive compound that causes seizures, has been shown to disrupt GABAergic signaling [125]. Application of the TP/AOP will not only enable us to better resolve the pathway/mechanisms/ risks for domoic acid, but similar assessments can be carried out for other chemicals that impact different points in the TP.…”
Section: Evaluating Model Predictive Capabilitiesmentioning
confidence: 98%
“…These culture systems are enriched in glutamatergic, cholinergic, and GABA-ergic neurons. The neurons mature at 6 to 10 days in culture, expressing functional receptors for NMDA and kainate [54,57,59,61,69] and releasing glutamate under depolarization [53]. When glutamate surpasses a concentration threshold, cell death occurs by a mechanism including NMDA receptors [53] or oxidative stress [54].…”
Section: Predictive In Vitro Assays For Excitatory Neurotoxinsmentioning
confidence: 99%
“…However, future research was recommended to provide similar exposures and outcomes to improve interpretation. Babot et al (2007) found that long-term exposure to dieldrin modified glutamatergic neurotransmission as a consequence of the prolonged decrease in γ-aminobutyric acid type A and N-methyl-D-aspartate receptor function in primary cultures of mouse cerebellar granule cells. Silver catfish (Rhamdia quelen) exposed for 96 hours to glyphosate presented an increase in the production of thiobarbituric acid reactive substances (TBARS) in muscle tissue, whereas the brain showed a decrease in TBARS (Glusczak et al, 2007).…”
Section: Miscellaneousmentioning
confidence: 98%
“…Banerjee et al (1999) reported functional modulation of GABAA receptors by Zn2+, pentobarbital, neuroactive steroid alphaxalone, and flunitrazepam in the cerebral cortex and cerebellum of rats undergoing status epilepticus induced by pilocarpine. Babot et al (2007) measured the reduction in mouse GABAA receptor function by 3 μM dieldrin using the GABA-induced 36Cl-uptake method. reviewed evidence for GABAA receptors in human and mammalian brains, whereas Narahashi (1996) and Costa (2015) reviewed organochlorine and some pyrethroid compounds as insecticides with the target site of chloride channel.…”
Section: How It Is Measured or Detectedmentioning
confidence: 99%